Pengaruh Pengetahuan Perpajakan dan persepsi atas penerapan sistem pembayaran pajak via e-commerce terhadap kepatuhan melalui kesadaran wajib pajak (studi kasus pada wajib pajak orang pribadi yang terdaftar di kpp pratama karawang utara) - muhamad iqbal; Asep Muslihat (AKUNTANSI DEWANTARA, 2021)
Tax revenues until the end of 2019 amounted to IDR 1.545,3 trillion, however, the level of compliance in terms of reporting taxes is still low, ranging from 60% to 70% and dominated by individual employee taxpayers. The lack of awareness of taxpayers in Indonesia is seen in the tax ratio percentage below 15% in the last five years. Tax knowledge is an important aspect in increasing compliance, considering that in the current digital era, the process of registering and paying taxes will always experience changes in terms of systems and procedures for implementing them. This can also form a perception for taxpayers on the payment system that is part of the Modul Penerimaan Generasi Ketiga (MPN-G3). This research uses descriptive and verification methods. The sample size is 100 respondents who are individual taxpayers, entrepreneurs or non-employees who are registered at KPP Pratama Karawang Utara. The analysis used in this research is scale range analysis and path analysis. Based on the research results, knowledge of taxation has a direct effect on individual taxpayer compliance and does not have an indirect effect through taxpayer awareness. Taxpayers' perception has a direct effect on taxpayer compliance and does not have an indirect effect through mandatory awareness